The Two Monetary Approaches to the Balance of Payments : Keynesian and Johnsonian - Polak, J. (IMF Working Papers; Working Paper ;, 2001)
This paper emphasizes the distinction between two 'monetary approaches to the balance of payments', one developed in the IMF, the other under the leadership of Harry Johnson in Chicago. The IMF approach is presented as an evolutionary development of the Kahn/Keynes multiplier model in an open economy. Johnson's approach is anti-Keynesian and self-proclaimed revolutionary. It posits the 'essentially monetary character' of the balance of payments. The IMF model tests satisfactorily as an explanation of income and imports over time. The long-run equilibrium approach of the Chicago model precludes statistical testing, and its short-run tests prove statistically meaningless.